DSP c.6310delA p.(Thr2104Glnfs*12) associates with arrhythmogenic cardiomyopathy, increased trabeculation, curly hair, and palmoplantar keratoderma - Heliö, Krista; Brandt, Eveliina; Vaara, Satu; Weckström, Sini; Harjama, Liisa; Kandolin, Riina; Järviö, Johanna; Hannula-Jouppi, Katariina; Heliö, Tiina; Holmström, Miia; Koskenvuo, Juha W. (Frontiers in Cardiovascular Medicine, 2023)
Background Pathogenic variants in DSP associate with cardiac and cutaneous manifestations including arrhythmogenic right ventricular cardiomyopathy, dilated cardiomyopathy, curly or wavy hair, and palmoplantar keratoderma (PPK). Episodes of myocardial inflammation associated with DSP cardiomyopathy might be confused in clinical work with myocarditis of other etiologies such as viral. Cardiac magnetic resonance imaging (CMR) may help in differential diagnosis. Methods and results This study comprised 49 Finnish patients: 34 participants from families with suspected DSP cardiomyopathy (9 index patients and 25 family members) and 15 patients with myocarditis. All 34 participants underwent genetic testing and cardiac evaluation, and 29 of them also underwent CMR. Participants with the DSP variant, numbering 22, were dermatologically examined. The 15 patients with myocarditis underwent CMR and were evaluated during their hospitalization. A heterozygous truncating DSP c.6310delA p.(Thr2104Glnfs*12) variant was confirmed in 29 participants. Only participants with the DSP variant had pacemakers and life-threatening ventricular arrhythmias. Of the participants with the DSP variant, 24% fulfilled cardiomyopathy criteria, and the median age at diagnosis was 53. Upon CMR, myocardial edema was found to be more common in patients with myocarditis. Both groups had a substantial percentage of late gadolinium enhancement (LGE). A ring-like LGE and increased trabeculation were observed only in participants with the DSP variant. All the studied participants with the DSP variant had PPK and curly or wavy hair. Hyperkeratosis developed before the age of 20 in most patients. Conclusions The DSP c.6310delA p.(Thr2104Glnfs*12) variant associates with curly hair, PPK, and arrhythmogenic cardiomyopathy with increased trabeculation. Cutaneous symptoms developing in childhood and adolescence might help recognize these patients at an earlier stage. CMR, together with dermatologic characteristics, may help in diagnosis.